2010
DOI: 10.1007/s00213-010-2107-1
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant–placebo differences in 16 clinical trials over 10 years at a single site: role of baseline severity

Abstract: Our results show that no diminution of drug-placebo difference occurs over time when baseline severity remains constant. As such, they support the importance of depression severity as a determinant of antidepressant-placebo difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
(14 reference statements)
2
9
0
Order By: Relevance
“…Specifically, our analysis was based on a drugplacebo difference on the HAM-D 17 that is on the high end of what has been detected in contemporary placebocontrolled antidepressant trials. The average drugplacebo difference on the HAM-D 17 for a number of effective antidepressants is approximately 2.0 (Khan et al, 2011), which is consistent with the mean difference observed for desvenlafaxine in the studies in this analysis. We chose to use the more stringent cutoff of 3.0 rather than 2.0 to effectively 'raise the bar,' as we try to better define 'clinically significant' improvements in functional outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…Specifically, our analysis was based on a drugplacebo difference on the HAM-D 17 that is on the high end of what has been detected in contemporary placebocontrolled antidepressant trials. The average drugplacebo difference on the HAM-D 17 for a number of effective antidepressants is approximately 2.0 (Khan et al, 2011), which is consistent with the mean difference observed for desvenlafaxine in the studies in this analysis. We chose to use the more stringent cutoff of 3.0 rather than 2.0 to effectively 'raise the bar,' as we try to better define 'clinically significant' improvements in functional outcomes.…”
Section: Discussionsupporting
confidence: 82%
“…The finding that antidepressants have modest symptom reducing effects relative to placebo has been replicated in several other studies (Khan et al, 2002, 2005, 2011; Fournier et al, 2010). The British consider the difference between placebo and antidepressant to be small enough to recommend that antidepressants not be used except in cases of severe depression (Bonin, 2012).…”
Section: Modest Efficacy Of Antidepressants During Treatmentmentioning
confidence: 65%
“…However, research in MDD has suggested that antidepressant efficacy may depend upon initial symptom severity. Both trial‐level (Khan, Leventhal, Khan, & Brown, ; Kirsch et al., ) and individual patient data (IPD) meta‐analyses (Fournier et al., ; Khan, Bhat, Faucett, Kolts, & Brown, ; Khan, Brodhead, Kolts, & Brown, ) have found that antidepressants are more effective for patients with high initial severity, with some of these analyses suggesting that efficacy is minimal for patients with mild depression (Fournier et al., ; Kirsch et al., ). Consequently, many guidelines no longer recommend antidepressants for mild depression (National Institute for Health and Care Excellence, ; Spijker et al., ).…”
Section: Introductionmentioning
confidence: 99%